A Significant Positive Association of Vitamin D Deficiency with Coronary Artery Calcification among Middle-aged Men: For the ERA JUMP Study. (2nd October 2016) - Lee, Sunghee; Ahuja, Vasudha; Masaki, Kamal; Evans, Rhobert W.; Barinas-Mitchell, Emma J. M.; Ueshima, Hirotsugu; Shin, Chol; Choo, Jina; Hassen, Lauren; Edmundowicz, Daniel; Kuller, Lewis H.; Willcox, Bradley; et al.
Abstract : Objective : Although a significant positive association of vitamin D deficiency with coronary heart disease has been demonstrated in cross-sectional as well as prospective studies, only a few studies have examined the association of vitamin D deficiency with subclinical atherosclerosis. We examined whether vitamin D deficiency is associated with subclinical atherosclerosis, as measured by coronary artery calcification (CAC) in asymptomatic adults. Methods : In a population-based cross-sectional study, 195 men aged 40 to 49 years without cardiovascular disease were randomly selected (98 Caucasian and 97 Japanese American men). Liquid chromatography–tandem mass spectrometry was utilized to measure serum vitamin D. CAC was examined by electron beam computed tomography using standardized protocols and read centrally at the University of Pittsburgh using Agatston's methods. To investigate an association between vitamin D deficiency (defined as 25-hydroxyvitamin D [25(OH)D] < 20 ng/mL) and CAC (defined as Agatston score ≥ 10), we utilized multivariable logistic regression models. Results : Prevalence of CAC and vitamin D deficiency was 27.2% and 10.3%, respectively. Participants with CAC were significantly older, had significantly higher body mass index (BMI), and had higher rates of smoking. Those with CAC were 3.31 times likely to be vitamin D deficient, after adjusting for traditional cardiovascular risk factors (odds ratio [OR] = 3.31, 95% confidence interval [CI], 1.12–9.77). Conclusions : In this population-based study of healthy middle-aged men, vitamin D deficiency had a significant positive association with the presence of CAC.